Pindorama of Mboîa and Îakaré: continuity and change in the trajectory of Tupi populations - Corrêa, Ângelo Alves (2023)
The aim of this article is to present the results of the analysis of 1,570 whole and half-whole ceramic vessels, understood in the light of 780 bibliographic sources and contextualized in the more than 5 thousand mapped archaeological sites, all related to people of the Tupi linguistic stock. Data on location, a chronology of archaeological sites, morphologies, and surface treatment of ceramics were used to contribute to the understanding and improvement of archaeological models in association with linguistic models and historical and ethnographic data. As a result, I present details about the differences and similarities in the ceramic sets of the regions occupied by the Tupi. This detailed picture made it possible to perceive the phenomena of continuity and change throughout its history, evidenced by the changes and persistence in cultural practices reflected in ceramics. Archaeological models of the Tupi are becoming more complex pari passu with the accumulation and analysis of data. In the 1980s, with Brochado, we left a Tupiguarani tradition plastered to the understanding of ceramic sets that reflected the history of people speaking Tupinamba and Guarani languages. Here, I present, in addition to these two groups, others individualized sets denominated as Tupi Norte-Ocidental, Tupi Norte-Oriental, and Proto-Tupinambá. With such complexification, the objective goes beyond presenting only the archaeological data, and it intends to present hypotheses about the long-term history of the populations of the Tupi stock.